PHARMACOLOGICAL EVALUATION OF FIVE MEDICINAL PLANTS IN LABORATORY ANIMALS (2011)
Medicinal plants have potential therapeutic characteristics, but most are yet to be pharmacologically evaluated. Tithonia diversifolia (Td), Acalypha wilkesiana (Aw), Lippia multiflora (Lm), Ocimum gratissimum (Og) and Morinda morindoides (Mm) are locally used for the treatment of malaria. The pharmacological and toxicological effects of the aqueous extract, solvent fractions (hydromethanol, hexane, chloroform and ethyl acetate) and Chromatographic sub-Fractions (CsF) A-F of these plants were assessed in rats and mice. Diabetes was alloxan - induced in rats. Antidiabetic effects of the aqueous leaf extracts of Td, Aw, Lm, Og, the root extract of Mm administered orally at a dose of 400 mg/kg for 21 days were evaluated in rats. Glibenclamide and distilled water were administered to equal number of rats as positive and negative controls, respectively. One hundred and ten rats comprising five per group of 22 were further exposed to 200 and 400 mg/kg doses of solvent fractions and 100 mg/kg CsF A-F of Mm and Aw. Isolation and purification of active compounds were carried out using bioactivity guided fractionation and accelerated gradient chromatography. Anti-inflammatory and analgesic effects of the aqueous extract, solvent fractions and CsF of the bioactive fraction of Mm were determined using the carrageenan induced rat paw model and acetic-acid induced writhing method in mice. Toxic effects of the aqueous extracts were assessed in rats at doses of 400, 800 and 1600 mg/kg for 28 days using haematology, serum biochemistry and organ pathology as indices. Phytochemical analyses of all the plants were carried out using standard methods. Isolation and purification of active compounds were carried out using standard procedures. Data were analyzed using descriptive statistics and ANOVA (p<0.05). The 400 mg/kg aqueous extract and chloroform CsF B at 100 mg/kg of Mm caused significant (56% and 74% respectively) reduction in blood sugar (BS) compared to positive control. The 400 mg/kg of aqueous and 100 mg/kg hexane CsF D of Aw caused 51 and 58% reductions in BS, respectively. The chloroform CsF A of Mm caused a significant (93%) reduction in rat paw oedema, while the ethyl acetate CsF D of Mm caused a 71% inhibition of writhing in mice. Haematology and serum biochemistry were normal; no histopathological changes were observed in all except Td; which caused statistically significant 70.1'12.4 and 141.1'2.7 ('/l) increases in ALP and ALT respectively at 400 mg/kg when compared with the control. Mm, Aw, Lm and Og contain alkaloids, saponins, flavonoids while Td contain glycosides, tannins, polyphenols and anthraquinones. Compounds 1 and 2 responsible for anti-inflammatory and BS reduction effect respectively were isolated from the chloroform fraction of Mm.Compound 3 with analgesic effect, was isolated from the ethyl acetate fraction of Mm. Compound 4 isolated from the hexane fraction of Aw also reduced BS. Active compounds isolated from Morinda morindoides had anti-diabetic, analgesic and anti-inflammatory effects while the compound isolated from Acalypha wilkesiana also had antidiabetic effect. Compounds 1 to 4 were isolated for the first time in this study.